Correlation between physical activity and acute respiratory infections in preschool children - Melika Melunović; Mirela Lisičić-Konaković; Belma Krdžalić–Zečević; Amela Kulašević; Lejla Kurtalić (Medicinski glasnik, 2025)
Aim: To analyse a correlation between physical activity (PA) and acute respiratory infections (ARIs) in preschool children aged 5 to 7 years. Methods: Data on both ARIs, sedentary behaviour (SB) and PA were obtained through specially created questionnaires for this study and relationships between them were examined. Results: A total of 129 children with an average age of 72.2±4.2 months, with a slightly higher number of males, 65 (50.4%), have participated in the study. Upper respiratory tract infections (URTIs) were in a significantly negative correlation with the frequency of training on weekdays (p=0.041) and weekends (p=0.005). Lower respiratory tract infections (LRTIs) had a significantly positive correlation with the frequency of usage of electronic gaming devices on weekdays (p=0.034), and a significant negative correlation with the frequency of spending time in nature on weekends (p=0.036). ARIs in total were in a significant negative correlation with the frequency of training on weekdays (p=0.025) and weekends (p=0.005). Conclusion: An increase of SB and reduced PA level showed a negative impact on the ARIs increase. It is recommended to introduce programs to increase PA among young children.
Keywords: child; exercise; preschool; respiratory infec-tions; sedentary behaviour